2016
DOI: 10.3847/0004-637x/831/1/52
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of a Milky Way-Sized Disk Galaxy. I. A Comparison of Numerical Methods

Abstract: The long-standing challenge of creating a Milky Way-like disk galaxy from cosmological simulations has motivated significant developments in both numerical methods and physical models. We investigate these two fundamental aspects in a new comparison project using a set of cosmological hydrodynamic simulations of a Milky Way-size galaxy. In this study, we focus on the comparison of two particle-based hydrodynamics methods: an improved smoothed particle hydrodynamics (SPH) code Gadget, and a Lagrangian Meshless … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 99 publications
(253 reference statements)
1
25
0
Order By: Relevance
“…We do note these tests have demonstrated that our default implementation can simultaneously accurately evolve phenomena including gas in regular or warped Keplerian discs, strong interacting shocks, current sheets and flux tubes, supersonic and subsonic turbulence, fluid mixing instabilities (Kelvin-Helmholz, Rayleigh Taylor, etc. ), multifluid dustgas dynamics, collisional+collisionless gravitational dynamics, and reproduces the correct linear growth rates of the magnetorotational instability (MRI) and non-ideal Hall MRI and anisotropic MHD instabilities (magnetothermal, heat-flux-bouyancy) (Hopkins 2015;Hopkins & Raives 2016;Zhu & Li 2016;Lupi, Volonteri & Silk 2017;Deng et al 2019a, b;Moseley et al 2019;Rennehan et al 2019;Hu & Chiang 2020;Panuelos, Wadsley & Kevlahan 2020). Tests of idealized problems involving self-gravitating MHD including the Evrard (1988) problem (spherical collapse of a self-gravitating polytrope), the MHD Zel'dovich (1970) pancake (self-gravitating collapse of an initially linear density perturbation along one dimension in a 3D Hubble flow) demonstrate that the MFM/MFV methods in GIZMO (as well as related moving-mesh methods) converge much more rapidly than popular AMR or SPH methods applied to the same problem (Hopkins 2015;Hopkins & Raives 2016;Hubber, Rosotti & Booth 2018).…”
Section: Existing Testsmentioning
confidence: 79%
“…We do note these tests have demonstrated that our default implementation can simultaneously accurately evolve phenomena including gas in regular or warped Keplerian discs, strong interacting shocks, current sheets and flux tubes, supersonic and subsonic turbulence, fluid mixing instabilities (Kelvin-Helmholz, Rayleigh Taylor, etc. ), multifluid dustgas dynamics, collisional+collisionless gravitational dynamics, and reproduces the correct linear growth rates of the magnetorotational instability (MRI) and non-ideal Hall MRI and anisotropic MHD instabilities (magnetothermal, heat-flux-bouyancy) (Hopkins 2015;Hopkins & Raives 2016;Zhu & Li 2016;Lupi, Volonteri & Silk 2017;Deng et al 2019a, b;Moseley et al 2019;Rennehan et al 2019;Hu & Chiang 2020;Panuelos, Wadsley & Kevlahan 2020). Tests of idealized problems involving self-gravitating MHD including the Evrard (1988) problem (spherical collapse of a self-gravitating polytrope), the MHD Zel'dovich (1970) pancake (self-gravitating collapse of an initially linear density perturbation along one dimension in a 3D Hubble flow) demonstrate that the MFM/MFV methods in GIZMO (as well as related moving-mesh methods) converge much more rapidly than popular AMR or SPH methods applied to the same problem (Hopkins 2015;Hopkins & Raives 2016;Hubber, Rosotti & Booth 2018).…”
Section: Existing Testsmentioning
confidence: 79%
“…Over the mass range simulated (M * ∼ 10 9 − 10 12 M ), the stellar mass functions agree very well at z > 1, but then begin to differ, with SPH tending towards smaller masses by ∼ 0.2 dex by z = 0. Yet another study using still different ISM and feedback models in GIZMO presented in Zhu & Li (2016), who see a similar "divergence" between MFM and some SPH flavors.…”
Section: (Significant) Effects In the Cgm Of Massive Galaxies' "Hot Hmentioning
confidence: 82%
“…This is critical for studies of angular momentum and rotational support in galaxies, as previous works have found significant spurious angular momentum loss due to numerical effects, particularly at low resolution (Governato et al 2004;Kaufmann et al 2007a). MFM resolves a number of numerical issues that have been shown to cause spurious angular momentum loss in galaxy formation simulations (Zhu & Li 2016;Hopkins et al 2017), including the unphysical cooling of cold low-angular momentum "blobs" from the hot halo into galaxies and numerical torques red between galaxies and their halos (e.g. Okamoto et al 2003;Agertz et al 2007;Torrey et al 2012;Kereš et al 2012;Few et al 2016).…”
Section: Simulationsmentioning
confidence: 99%